Blood culture-negative endocarditis: Improving the diagnostic yield using new diagnostic tools. Issue 47 (November 2017) - Fournier, Pierre-Edouard; Gouriet, Frédérique; Casalta, Jean-Paul; Lepidi, Hubert; Chaudet, Hervé; Thuny, Franck; Collart, Frédéric; Habib, Gilbert; Raoult, Didier
Abstract : Abstract: Blood culture-negative endocarditis (BCNE) may represent up to 70% of all endocarditis cases, depending on series. From 2001 to 2009, we implemented in our laboratory a multimodal diagnostic strategy for BCNE that included systematized testing of blood, and when available, valvular biopsy specimens using serological, broad range molecular, and histopathological assays. A causative microorganism was identified in 62.7% of patients. In this study from January 2010 to December 2015, in an effort to increase the number of identified causative microorganisms, we prospectively added to our diagnostic protocol specific real-time (RT) polymerase chain reaction (PCR) assays targeting various endocarditis agents, and applied them to all patients with BCNE admitted to the 4 public hospitals in Marseille, France. A total of 283 patients with BCNE were included in the study. Of these, 177 were classified as having definite endocarditis. Using our new multimodal diagnostic strategy, we identified an etiology in 138 patients (78.0% of cases). Of these, 3 were not infective (2.2%) and 1 was diagnosed as having Mycobacterium bovis BCG endocarditis. By adding specific PCR assays from blood and valvular biopsies, which exhibited a significantly greater sensitivity ( P < 10 −2 ) than other methods, causative agents, mostly enterococci, streptococci, and zoonotic microorganisms, were identified in an additional 27 patients (14 from valves only, 11 from blood only, and 2 from both). Finally, in another 107 patients, a pathogen was detected using serology in 37, valve culture in 8, broad spectrum PCR from valvular biopsies and blood in 19 and 2, respectively, immunohistochemistry from valves in 3, and a combination of several assays in 38. By adding specific RT-PCR assays to our systematic PCR testing of patients with BCNE, we increased the diagnostic efficiency by 24.3%, mostly by detecting enterococci and streptococci that had not been detected by other diagnostic methods, but also agents requiring specific management such as Mycoplasma hominis and Tropheryma whipplei . Abstract : Supplemental Digital Content is available in the text